Cyclic Acetalization of Furfural on Porous Aluminosilicate Acid Catalysts - Hartati Hartati; Didik Prasetyoko; Mardi Santoso (Universitas Gadjah Mada, 2016)
Porous aluminosilicate materials included microporous and mesoporous ZSM-5, hierarchical aluminosilicates, and mesoporous aluminosilicate were tested for acetalization of furfural (furan-2-carbaldehyde) with propylene glycol. The existing synthesis methods for aluminosilicate and ZSM-5 were modified to produce aluminosilicate material with hierarchical porous structure. Catalytic activity in acetalization of furfural by propylene glycol were conducted by refluxed of the mixture of furfural, propylene glycol and catalyst, using toluene as solvent and nitrobenzene as internal standard, at 106 °C for 4 h. The result showed that a combination of two structure directing agents, tetrapropylammonium hydroxide (TPAOH) and cetyltrimethylammonium bromide (CTAB) and modification of catalytic crystallization produced an active aluminosilicate framework that provides a wide access for a bulky reactants and strong acid sites to catalyze the reaction. The pore structure and the strength of the Brønsted acid sites were crucial for the high conversion of furfural to produce a cyclic acetal.